(untitled) (INTERNATIONAL CONFERENCE ON MEDICINE, SCIENCE, AND EDUCATION, 2024)
This article describes the results of the research conducted on optimizing the organoleptic characteristics of bread products made from corn flour. In this, scientifically based conclusions were made on determining the optimal proportions of bread making by mixing wheat flour with oat flour.